2014
DOI: 10.1007/s10157-014-0998-6
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil suppresses urinary protein excretion and activates eNOS in Dahl salt-sensitive hypertensive rats

Abstract: In DS rats fed a HS diet, nicorandil prevented the development of renal dysfunction, which was accompanied by an increase in eNOS expression in the kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The decrease in the iNOS expression in Group 3 may be due to antioxidant and anti‐inflammatory effects of nicorandil. As stated in the study of Tashiro et al [30], nicorandil increases eNOS expression, and the increase in eNOS activity may also contribute to the renoprotective effect of nicorandil.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The decrease in the iNOS expression in Group 3 may be due to antioxidant and anti‐inflammatory effects of nicorandil. As stated in the study of Tashiro et al [30], nicorandil increases eNOS expression, and the increase in eNOS activity may also contribute to the renoprotective effect of nicorandil.…”
Section: Discussionmentioning
confidence: 75%
“…The renoprotective effects of nicorandil have been reported in several models, such as renal ischemia–reperfusion, diabetic nephropathy, and remnant kidney [30]. Previous research reported that nicorandil acted as both a nitrovasodilator and potassium channel opener.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, another study showed that in a rat remnant kidney model of chronic kidney disease, treatment with nicorandil preserved renal function by blocking oxidative stress‐related injury of podocytes and macrophages . Moreover, recent evidence from study in Dahl salt‐sensitive hypertensive rats showed that nicorandil prevented the development of renal dysfunction with the suppression of urinary protein excretion and the activation of endothelial nitric oxide synthase . Taken together, nicorandil may protest against the incidence of CIN via various possible mechanisms, and future studies are needed to clarify the exact molecular pathways underlying the preventative efficacy of nicorandil against CIN.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that examined the role of eNOS as a potential mechanism for the improvement of adenine with nicorandil. However, Date et al (2005), Hongo et al (2005) and Tashiro et al (2015) showed that nicorandil increased endotheliumderived NO production by activation of eNOS, inhibited endothelial cell death, and exerted anti-inflammatory and antioxidative effects and this may contribute to the protective effect of nicorandil.…”
Section: Control Control Adeninementioning
confidence: 98%